Avaliação de diferentes metodologias na determinação do valor nutricional da glicerina e níveis de inclusão em dietas para suínos - Leite, Rafaeli Gonçalves (2016)
Seeking nutritional alternatives to maintain economic viability and the nutritional quality of diets for pigs , several studies consider the use of co- products such as glycerine. Thus, in Chapter 1 , a review was carried out about getting glycerin , features and metabolism of glycerol , the possibilities and limitations of its use . In Chapter 2 , conducting an experiment was reported to determine the nutritional value of glycerin by using the total collection method of feces and urine , and the indicator method using chromium oxide , with treatments consisting of diet reference diet containing 10% glycerin and diet containing 10 % glycerin " on top" . In chapter 3 it was reported conducting an experiment on the performance of pigs in the finishing phase fed diets containing glycerin and influence of treatments on carcass traits and meat , the animals were fed diets with glycerin at levels of 0 , 5, 10 to 15%. The glycerin obtained from soy oil presented 3.443 and 3.411 Kcal/ kg of digestible energy and 3.355 and 3.293 Kcal/ kg metabolizable energy determined by total collection method and indicator respectively and can be used in the conventional manner and "on top" .Glycerin can be used in finishing swine diets without compromising performance results of these animals to the inclusion of 15 %. Most carcass characteristics and pork meat were not changed when the animals were fed a diet containing up to 15 % glycerin. Hot carcass weight , carcass yield and standard L* color present their higher values when pigs are fed 2.32 ; 2.43 and 2.61 % glycerin in the diet, respectively.